2005
DOI: 10.1152/ajpcell.00076.2005
|View full text |Cite
|
Sign up to set email alerts
|

HAI-1 regulates activation and expression of matriptase, a membrane-bound serine protease

Abstract: Hepatocyte growth factor activator inhibitor-1 (HAI-1) was initially identified as cognate inhibitor of matriptase, a membrane-bound serine protease. Paradoxically, HAI-1 is also required for matriptase activation, a process that requires sphingosine 1-phosphate (S1P)-mediated translocation of the protease to cell-cell junctions in human mammary epithelial cells. In the present study, we further explored how HAI-1 regulates this protease. First, we observed that after S1P treatment HAI-1 was cotranslocated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
149
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(159 citation statements)
references
References 30 publications
(42 reference statements)
5
149
0
Order By: Relevance
“…In the present study, we found that HAI58K-R260A was detected at a low level in the co-expression with WT-matriptase (Fig. 4), this being consistent with the observation that R260L HAI-1 was produced poorly in the co-expression with matriptase (Oberst et al 2005). It is plausible that the HAI58K-R260A variant, which lacks matriptase-inhibitory activity (Kojima et al 2008), is susceptible to degradation by the protease.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In the present study, we found that HAI58K-R260A was detected at a low level in the co-expression with WT-matriptase (Fig. 4), this being consistent with the observation that R260L HAI-1 was produced poorly in the co-expression with matriptase (Oberst et al 2005). It is plausible that the HAI58K-R260A variant, which lacks matriptase-inhibitory activity (Kojima et al 2008), is susceptible to degradation by the protease.…”
Section: Discussionsupporting
confidence: 91%
“…It has been found that, when full-length matriptase cDNA is transfected alone into human breast carcinoma BT549 cells, the enzyme is poorly produced and retained in the endoplasmic reticulum and Golgi apparatus and that the trafficking defect is corrected by co-expression of full-length HAI-1 (Oberst et al 2005). We also found in a transient-expression system using monkey kidney COS-1 cells that fulllength rat matriptase (hereinafter, called WT-matriptase, see Fig.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…It has been shown in a transient-expression system using human breast cancer BT549 cells that hepatocyte growth factor activator inhibitor type I (HAI-1), the cognate inhibitor of matriptase, is required for the proper intracellular trafficking of the protease (Oberst et al 2005). Indeed, when expressed alone in this cell line, matriptase was retained in the endoplasmic reticulum and Golgi apparatus.…”
Section: Introductionmentioning
confidence: 99%